DETERMINAN PENINGKATAN KINERJA BISNIS : MODEL KONTINJENSI AKUNTANSI MANAJEMEN STRATEGIK - Nurhidayah Nurhidayah; Ismail Badollahi (Al-Buhuts, 2022)
The purpose of this research is to examine the determinants that can improve business performance. Theoretically, the characteristics of managers and competition are determinants that have an effective impact on improving business performance, especially for MSME entities, but in practice these determinants cannot work without conditional factors to support business performance improvement. The contingency approach is a strategic management accounting point of view that is appropriate in explaining how each determinant of business performance can work effectively. This research is explanatory research that uses a survey approach to test a research model. The research sample is MSME actors in Gowa Regency with criteria that meet the requirements to answer the survey instrument. The results of the study found that strategic management accounting has a direct effect on business performance. In addition, competition affects business performance through strategic management accounting. However, the characteristics of managers do not affect business performance through strategic management accounting. This can be used as a motivation for business people to continue to carry out self-development by way of business training, continue to add insight and experience and continue to innovate product development, in this way it is expected to improve business performance. Keywords: business performance, contingencies, strategic management accounting